The centre cannot (always) hold: Examining pathways towards energy system de-centralisation. (February 2020) - Judson, E.; Fitch-Roy, O.; Pownall, T.; Bray, R.; Poulter, H.; Soutar, I.; Lowes, R.; Connor, P.M.; Britton, J.; Woodman, B.; Mitchell, C.
Abstract: 'Energy decentralisation' means many things to many people. Among the confusion of definitions and practices that may be characterised as decentralisation, three broad causal narratives are commonly (implicitly or explicitly) invoked. These narratives imply that the process of decentralisation: i) will result in appropriate changes to rules and institutions, ii) will be more democratic and iii) is directly and causally linked to energy system decarbonisation. The principal aim of this paper is to critically examine these narratives. By conceptualising energy decentralisation as a distinct class of socio-technical transition pathway, we present a comparative analysis of energy decentralisation in Cornwall, South West UK, the French island of Ushant and the National Electricity Market in Australia. We show that, while energy decentralisation is often strongly correlated with institutional change, increasing citizen agency in the energy system, and enhanced environmental performance, these trends cannot be assumed as given. Indeed, some decentralisation pathways may entrench incumbent actors' interests or block rapid decarbonisation. In particular, we show how institutional context is a key determinant of the link between energy decentralisation and normative goals such as democratisation and decarbonisation. While institutional theory suggests that changes in rules and institutions are often incremental and path-dependent, the dense legal and regulatory arrangements that develop around the electricity sector seem particularly resistant to adaptive change. Consequently, policymakers seeking to pursue normative goals such as democratisation or decarbonisation through energy decentralisation need to look beyond technology towards the rules, norms and laws that constitute the energy governance system. Highlights: 'Energy decentralisation' can have multiple, sometimes contradictory interpretations. Incremental institutional change lags rapid advancements in technologies. Energy decentralisation can, but does not always, align with other normative goals. Pathways towards decentralisation are highly context specific and contingent on power dynamics among actors. A more detailed conceptualisation of roles than the incumbent/new entrant dichotomy may be needed.